Simulations of microwave characteristics of high-temperature superconducting microstrip lines by using an empirical two-fluid model. - Chien-Jang Wu
A numerical analysis of the microwave propagation characteristics of a high-temperature superconducting microstrip transmission line is presented. It is based on the transmission line theory and empirical two-fluid model which appropriately incorporates the quasiparticle scattering and residual loss of the superconductor. First, the calculated attenuation constant and phase velocity are compared with those predicted by the conventional two-fluid model for a YBa2Cu3O7-δ microstrip line with a linear substrate, lanthanum aluminate, LaAlO3. Next, we have specifically investigated the effects of nonlinear substrate such as strontium titanate, SrTiO3, on the attenuation constant and phase velocity. The tunable feature of such a microwave device owing to the nonlinear dielectric ferroelectric is illustrated and discussed.
Keywords: HTSC microstrip transmission line; Q-value.; YBaCuO; Attenuation constant; Empirical two-fluid model; Loss tangent; Microwave propagation characteristics; Nonlinear dielectric ferroelectric; Nonlinear permittivity; Nonlinear substrate effects; Phase velocity; Quasiparticle scattering; Relative permittivity; Residual loss; Transmission line theory; Tunable feature; LaAlO3.